Multidimensional Approach to Common Gastrointestinal Symptom - Nausea and Vomiting (Homoeopathy for All, 2025)
Nausea and vomiting are symptoms of many different health conditions, including early pregnancy, concussions and the stomach flu. Happening in both adults and children, there are many ways to relieve nausea. This article review is about causes, risk factors, different type, clinical presentation general management including some home remedies management and homoeopathic way of treatment of Nausea and vomiting. Homoeopathy treats the person as a whole. It means that homoeopathic treatment focuses on the patient as a person, as well as his pathological condition.
Keywords: Vomiting; common causes